The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1088/1755-1315/919/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of redclaw crayfish Cherax quadricarinatus von Martens 1868 using 16S mitochondrial DNA marker

Abstract: There have been reported around 11 aquatic invasive alien species (IAS) found in Malaysian waters. Cherax quadricarinatus, or commonly known as Australian redclaw crayfish, is one of the invasive species. C. quadricarinatus has the potential of causing negative impacts ecologically and economically in the local environment as it has reported in several countries if they get established and not monitored properly. Habitat alteration, native species depletion and spreading of diseases are among the reported nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another study published by the same authors also reported that global changes such as increased water pollution and changes in water chemistry are making it more difficult for crayfish to find food and reproduce successfully [ 65 ]. In addition, another study from 2020 [ 36 , 62 ] reported that the spread of invasive species is also impacting native crayfish populations, leading to declines in abundance, distribution, and genetic diversity. Overall, these studies show that global changes are detrimental to crayfish populations and may lead to their decline or extinction if steps are not taken to address these issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study published by the same authors also reported that global changes such as increased water pollution and changes in water chemistry are making it more difficult for crayfish to find food and reproduce successfully [ 65 ]. In addition, another study from 2020 [ 36 , 62 ] reported that the spread of invasive species is also impacting native crayfish populations, leading to declines in abundance, distribution, and genetic diversity. Overall, these studies show that global changes are detrimental to crayfish populations and may lead to their decline or extinction if steps are not taken to address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…In this scientometric analysis, the descriptive and co-citation datasets were generated to explain the current knowledge of the selected research themes. Notably, the topics focused on crayfish in the published reviews ranged from the aquacultural potential of crayfish [ 4 , 24 ], environmental and culturing practices [ 25 , 26 ], records of their introduction in the European and African regions [ 27 , 28 ], and crayfish-related diseases [ 26 , 29 , 30 , 31 , 32 ] to ecological interactions and biodiversity [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…IAS might replace native organisms and potentially alter ecosystems and disrupt food chains while reducing and destroying the genetic diversity of indigenous species [63]. As Dali et al [64] mentioned, the introduction of IAS has made the study of genetic diversity vital. The presence of an invasive species, particularly in native inland waters, is considered a major challenge for the protection and preservation of local fish biodiversity [62,65].…”
Section: Introductionmentioning
confidence: 99%